Openness, Wage Gaps and Unions in Chile A Micro Econometric Analysis - Friedman, Jorge (OECD Trade Policy Papers, 2011)
This paper examines the relationship between wages and levels of trade and FDI openness in twenty-nine sectors of the Chilean economy. Over the last four decades, this country almost fully liberalized its trade and foreign direct investment, which accelerated growth of flows in both areas and contributed to important changes in the labour market. Using cluster analysis, we divide 29 sectors into three groups of high, medium and low levels of trade and foreign direct investment penetration in 2003 and 2008. Subsequently, an average wage equation is estimated for salaried workers in each group based on their characteristics (gender, education, work experience and union membership) using microdata of the Supplementary Income Survey (SIS) database. Differences between average wages of the three groups are decomposed with the Oaxaca-Blinder method. The results confirm that the group of most open sectors pays a "wage premium" to its workers. It is also shown that most of this premium is accounted for by higher levels of labour unionisation compared to other sectors. An alternative grouping of sectors into two categories of tradable and non-tradable sectors based on export intensity only yields similar results